Cher ‘earth’ in Tuvan paroemias - Suvandii, Nadezhda D. (The New Research of Tuva, 2023)
The article examines a concept of the Tuvan culture — ‘чер’ (‘earth’). The researcher analyzes its meanings and aspects using proverbs and sayings from different collections. Unlike other linguoculturologists who are focused on studying the concept ‘native land, Motherland’ (‘төрээн чер, төрээн чурт’ in Tuvan), the author discusses a broader concept. The work was carried out within the framework of the study of the main concepts that make up the thesaurus of Tuvan culture. In particular, it is noted that there is a difference between the meanings of the terms ‘чер’ and ‘чурт’, which is almost not discussed by philologists. One of the facets of the concept ‘чер’ is the aspect of the proximity of the earth to man, the kinship between them: the earth is the mother, it is the native land. In another aspect, the beliefs about the earth formulated in proverbs also contain an understanding of its fertility. Since the land was of great importance to the Tuvans, its qualities and characteristics were constantly compared with what people do or what they are.